The Clue in the Secret Passage B.7 - Thomas, Jerry D.; Nang Chan Yeema (Nampa, ID USA Pacific Press Publishing Association, 1997)
When DeeDee and her family go to stay at her ailing grandmother's scary old house and their treasured family Bible is lost, the ensuing search leads to some discoveries about past race rations in Mill Valley.
Keywords: Story Collection